Negotiation and Contestation of Islamic Religious Practices of the Transvestites in Yogyakarta - Dony Arung Triantoro; Ardiansyah Ardiansyah (Universitas Muhammadiyah Magelang, 2018)
This paper analyzes the forms of negotiation and contestation of religious practices Transvestites in Yogyakarta. The issue of Transvestites has become a hot conversation in the Indonesian public space and has led to multiple interpretations of the Transvestites identity’s position in the eyes of the law, religion, and society. So, it becomes significant to see how the negotiation and contestation of the Islamic religious practices among Transvestites. This study was conducted through field studies by conducting in-depth interviews and relevant literature search both online and offline. The results indicate that the Contestation of Islamic practices among Transvestites occurs in the form of interpretation of the Quranic texts, families and community organizations. To strengthen its existence, transvestites carried out many negotiations mainly related to the Islamic practice. Negotiations are carried out through various activities such as holding regular recitations, engaging in discussion forums and social activities in the community and interpreting the Quranic verse with a dehumanization approach to Islamic law. Besides, the support of religious leaders and the Legal Aid Institute further strengthens its authority in the community.